A compensação dos gestores, a sustentabilidade empresarial e os impactos no desempenho, valor e risco das empresas brasileiras - Guimarães, Thayse Machado (2014)
In a competitive business environment, like nowadays, the corporate governance and corporate sustainability issues arise as a way to improve companies image and credibility. It is believed that the study of managers compensation and corporate sustainability provides reflections about the problem of the agency theory, as well as a better understanding of the stakeholder theory and the search for long-term value. In this way, this research analyzes the influence of corporate sustainability in the compensation of managers, and the influence of these variables in performance indicators, risk and value of Brazilian companies listed on the BM&FBovespa. The research involved the period 2009-2013, because with the CVM instruction 480 in 2009, publicly traded companies were required to submit detailed information about directors remuneration. It is assumed, therefore, that companies that are listed on the BM&FBovespa\'s Corporate Sustainability Index (ISE) are concerned with the welfare not only of the shareholders, but also employees, suppliers and other partners. Thus, it is expected that these companies also grant better compensation to its managers. Regarding this last aspect, other variables were used in addition to the fixed remuneration paid to executives, which were aggregated into an index, using the technique of principal component analysis. To perform the analysis of the proposed relationships, we carried out a set of panel data regression models. The results shown that it s possible to infer that companies listed on the ISE tend to secure better compensation to its managers. Furthermore, organizations that provide better compensation to its managers typically have better indicators of accounting performance, higher market value, lower total risk (volatility), lower systematic risk (beta) and higher risk of internal capital structure (WACC). Besides, the companies listed on the ISE generally provide lower volatility of returns (lower total risk). Thus, the results suggest that organizations concerned with the reconciliation of the different interests of its stakeholders tend to be more valued by the market in the long run.